Anemia and the use of antihypertensive medications in hemodialysis patients: multicenter retrospective observational study - N. Stepanova; V. Novakivskyy; L. Snisar; M. Kutsenko (Ukrainian Journal of Nephrology and Dialysis, 2019)
Abstract. We hypothesized that the use of antihypertensive medications in patients treated by hemodialysis (HD) may interfere with the activity of erythropoietin and leads to an increase in the dose of erythropoiesis stimulating agents (ESAs).The aim of our study was to analyze the impact of antihypertensive medications on the effectiveness of anemia treatment.Methods. We conducted a multicenter retrospective observational study. The archival medical data from 379 patients treated by HD or hemodiafiltration (HDF) were used. The medical records of 142 patients were excluded from the study. The study group consisted of 237 patients: 108 (45.6%) women and 129 (54.4%) men, with an average age of 54 [41-62.5] years.Results. The analysis of the mean hemoglobin (Hb) stratified by the administration of antihypertensive medications in the dynamics of dialysis treatment demonstrated a significant impact of angiotensin-converting enzyme (ACE) inhibitors (F = 3.97; p = 0.048) and amlodipine (F = 6.9; p = 0.01) on the effectiveness of anemia correction. The significant effect of amlodipine on the need to increase the dosage of iron-containing medications (OR = 3.9; 95% CI (1.27-12.06), p = 0.002; RR = 1.9 95% CI (1.27-2.9) and continuous erythropoietin receptor activator (CERA) (OR = 5.2, 95% CI (1.2-24.4), p = 0.03; RR = 1.3 95% CI (1, 08-1.6), p = 0.006) weas showed by logistic regression analysis. The increased risk of failure to achieve of the target Hb level in HD patients received amlodipine was confirmed by Cox regression model (HR = 2.7 (95% CI 1.5-4.7)).Conclusions: The results of our study demonstrated a significant increase in the frequency of appointment and amount of anti-anemia therapy in HD patients when amlodipine is co-administered. Follow-up studies to determine the effect of amlodipine mechanism for anemia will avoid unreasonable prescriptions for the treatment of НD patients.Conflict of interest statement: the authors declared no competing interests.